2022
DOI: 10.1093/cid/ciac430
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Heterologous Coronavirus Disease 2019 (COVID-19) Vaccine Booster Dosing in Brazilian Healthcare Workers, 2021

Abstract: Objectives Little is currently known about vaccine effectiveness (VE) for either two doses of Oxford-AstraZeneca (ChAdOx1) viral vector vaccine or CoronaVac inactivated viral vaccine followed by a third dose of mRNA vaccine (Pfizer/BioNTech) among healthcare workers (HCWs). Methods We conducted a retrospective cohort study among HCWs (aged ≥18 years) working in a private healthcare system in Brazil from January to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…All studies concluded that homologous and heterologous booster doses significantly increase concentrations of different anti-SARS-CoV-2 antibodies (and sometimes cell-mediated immunity). 16 , 17 , 18 Studies comparing homologous versus heterologous booster responses among individuals receiving primary inactivated vaccines (mostly CoronaVac in China, Brazil, Turkey, and Thailand 19 , 20 , 21 , 22 ) report a more robust response with heterologous boosters. An antibody study from Brazil 23 and one effectiveness study from Chile 24 provided the most robust evidence for this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…All studies concluded that homologous and heterologous booster doses significantly increase concentrations of different anti-SARS-CoV-2 antibodies (and sometimes cell-mediated immunity). 16 , 17 , 18 Studies comparing homologous versus heterologous booster responses among individuals receiving primary inactivated vaccines (mostly CoronaVac in China, Brazil, Turkey, and Thailand 19 , 20 , 21 , 22 ) report a more robust response with heterologous boosters. An antibody study from Brazil 23 and one effectiveness study from Chile 24 provided the most robust evidence for this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, unfortunately, the spike and non-neutralizing viral antibody levels of participants were not available. Nonetheless, the FDA does not advise antibody testing to evaluate immunity or protection from COVID-19, particularly among those who had vaccination [ 29 ]. Finally, our data exclude vaccine effectiveness against the Omicron variant and may not be generalized to the current status of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Data to assess the effectiveness of heterologous booster schedules, however, are sparse and mainly limited to studies conducted during periods of delta variant predominance and/or as compared with unvaccinated. [10][11][12][13][14][15]17,18] To our knowledge, no study has reported the effectiveness of the individual heterologous booster schedules with the AZD, BNT, and MOD vaccines as compared with primary schedules during an omicron period. When compared with unvaccinated, heterologous and homologous schedules showed similar levels of improved protection against omicron infection [17] and severe COVID-19 [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies during delta predominance periods overall found improved protection of heterologous boosters compared with primary schedules, a protection that was comparable to the homologous boosters when indirectly compared. [10][11][12][13] However, the protection against severe COVID-19 was typically not analysed in these studies or the number of cases was very low precluding statistical precision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation